Respuesta :
First, you have to distribute the -1 throughout the parentheses, which gives you 7x-3x-10=-46.
Then, you combine 7x and -3x, which gives you 4x-10=-46.
Then, you add 10 to both sides of the equation, which gives you 4x=-36.
FInally, you divide both sides of the equation by 4, which gives you x=-9.
Answer:
x = -9
Step-by-step explanation:
7x - (3x + 10) = -46 (original problem)
7x - 3x - 10 = -46 (distributive property)
4x - 10 = -46 (combine like terms)
+10 +10 (inverse operation)
4x = -36 (addition)
1/4 x 4x = -36 x 1/4 (inverse operation)
x = -9 (multiplication)